Evaluasi Nilai Difusifitas Pelarut dan Konstanta Kecepatan Ekstraksi pada Isolasi Piperin Lada Hitam - Mega Mustikaningrum; Desty Arista; Retno Dwi Nyamiati; Dodi Eko Nanda (Eksergi, 2023)
Piperine is a type of bioactive compound that can be isolated from black pepper. Currently the utilization of piperine is dominated by the health sector. In this study, piperine was isolated using the Soxhlet method. The purpose of this research is to propose a mathematical model to determine the value of the diffusivity (DA) of piperine, the extraction rate constant (k) and the piperine isolation equilibrium constant for commercial designs. Based on the results obtained the value of DA was obtained at 0.1878 m2/minute, the value of k was obtained at 0.0012 m/minute and the value of K was obtained at 0.900. Extraction was carried out using 96% ethanol solvent with a ratio of 25:1 to black pepper samples using the soxhletation method of 5 circulations. The resulting piperine extract was 55.46 mol/liter